Efficient market hypothesis : evidence from asean-5 countries - Wong, Yeong Der (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This study applies a number of univariate unit root tests (conventional unit root tests and Lagrange Multiplier (LM) unit root test with two breaks) for time series data to determine the efficient market hypothesis (EMH) in five ASEAN countries which consists of Indonesia, Malaysia, Philippines, Thailand and Singapore. The daily closing price spanning from January 2, 1997 until December 31, 2010 for each of the countries is utilized the stationarity tests. The study found that both the conventional unit root tests and LM unit root test with two breaks failed to reject the random walk hypothesis. This implies all the tested stock markets are non-stationary and efficient under weak form hypothesis. On the other hand, the break dates detected endogenously under LM unit root test occur around the actual market crash date.